Quality of life assessment in children before and after a successful ablation for supraventricular tachycardia. (18th February 2020) - Gonzalez Corcia, M Cecilia; Peters, Laura; Sluysmans, Thierry; Moniotte, Stephane; Carbonez, Karlien; Barrea, Catherine; Vo, Christophe; Vanhoutte, Laetitia; Scavee, Christophe
ABSTRACT: Background and Objectives: Young patients suffering from rhythm disorders have a negative impact in their quality of life. In recent years, ablation has become the first-line therapy for supraventricular arrhythmias in children. In the light of the current expertise and advancement in the field, we decided to evaluate the quality of life in young patients with supraventricular arrhythmias before and after a percutaneous ablation procedure. Methods: The prospective cohort consisted of patients <18 years with structurally normal hearts and non-pre-excited supraventricular arrhythmias, who had an ablation in our centre from 2013 to 2018. The cohort was evaluated with the PedsQL ™ 4.0 Generic Core Scales self-questionnaire prior to and post-ablation. Results: The final cohort included 88 patients consisted of 52 males (59%), with a mean age at ablation of 12.5 ± 3.3 years. Forty-two patients (48%) had a retrograde-only accessory pathway mediating the tachycardia, 38 (43%) had atrio-ventricular nodal re-entrant tachycardia, 7 (8%) had ectopic atrial tachycardia, and 1 (1%) had atrial flutter. The main reason for an ablation was the patient's choice in 53%. There were no severe complications. Comparison between the baseline and post-ablation assessments showed that patients reported significant improvement in the scores for physical health, emotional and social functioning, as well as in the total scores. Conclusions: The present study demonstrates that the successful treatment of supraventricular arrhythmias by means of an ablation results in a significant improvement in the quality of self-reported life scores in young patients.